USING BIOPELLETS WITH METFORMIN IN THE EXPERIMENTAL METABOLIC SYNDROME - Voloshchuk, N.I.; Zolotareva, V.G.; Hara, A.V.; Pashynska, O.S.; Taran, I.V.; Melnyk, A.V.; Denysiuk, V.O. (World of Medicine and Biology, 2024)
The global prevalence of metabolic syndrome in Ukraine and the world gives reason to consider it one of the most dangerous diseases of the modern world. One of the promising directions in the pharmacotherapy of pathological conditions is the use of the drug in the form of bioidentical implants that contain a medicinal substance. Experimental metabolic syndrome in animals was modeled with the help of a Cafeteria diet, which imitated the problematic eating patterns of modern humans. Animal body weight, blood glucose, lactate and insulin content, HOMA index, and lipid metabolism indicators were evaluated as markers of metabolic syndrome and criterion signs of treatment effectiveness. Results showed that a 6-week Cafeteria diet causes a metabolic imbalance and is accompanied by signs characteristic of metabolic syndrome. Probable signs of insulin resistance accompanied these changes. Both the tablet and pellet form of the drug positively affected the indicators of carbohydrate metabolism and reduced the manifestations of insulin resistance. Metformin in bioidentical implants also significantly improved experimental animals’ general condition and appearance.